2004
DOI: 10.1161/01.res.0000128405.83582.2e
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Activation by Hypoxia in Pulmonary Arterial Smooth Muscle Cells Is Age and Site Specific

Abstract: Abstract-Hypoxia induces vasoconstriction of pulmonary arteries through contraction of smooth muscle cells (SMCs).The GTPase RhoA regulates smooth muscle contractility and actin cytoskeletal remodeling through the Rho-associated kinase (ROCK). We previously found that the postnatal fall in pulmonary vascular resistance was associated with actin cytoskeletal remodeling in porcine pulmonary arterial SMCs (PASMCs) in vivo. Here, we investigated the effects of acute and chronic hypoxia on the morphology and RhoA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…This response to U46619 in p62 Ϫ/Ϫ mice PA is similar to that observed in 2-week-old piglet PAs after inhibition of PKC (i.e., contraction without [Ca 2ϩ ] i signal) (Cogolludo et al, 2005). In these animals, there is an up-regulation of Rho kinase (Bailly et al, 2004), a key enzyme in Ca 2ϩ -sensitizing mechanisms. In addition, Rho kinase inhibitors were more effective inhibiting U46619 contractions in these piglets than in newborn piglets or adult rats (Cogolludo et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
“…This response to U46619 in p62 Ϫ/Ϫ mice PA is similar to that observed in 2-week-old piglet PAs after inhibition of PKC (i.e., contraction without [Ca 2ϩ ] i signal) (Cogolludo et al, 2005). In these animals, there is an up-regulation of Rho kinase (Bailly et al, 2004), a key enzyme in Ca 2ϩ -sensitizing mechanisms. In addition, Rho kinase inhibitors were more effective inhibiting U46619 contractions in these piglets than in newborn piglets or adult rats (Cogolludo et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
“…Phenotypic changes in response to hypoxia have been described previously in porcine, bovine, and rat conduit pulmonary arteries (18 -20). In SMC isolated from conduit arteries of neonatal piglets exposed to 11 d hypoxia, a stable change in SMC phenotype, manifested by a change in cell shape and regulation of the actin cytoskeleton, accompanied altered functional responses (21). Conduit vessels are composed of heterogenous SMC populations, but we found little structural variation between cells in the walls of resistance arteries, confirming previous studies (2) showing that the pulmonary resistance arteries of calves also have a homogeneous SMC population (22).…”
Section: Hypoxic Pulmonary Resistance Arteriessupporting
confidence: 87%
“…Our observation of the Rho-kinase inhibitors Y-27632 and hydroxyfasudil concentration dependently decreasing tone of KClprecontracted chicken DA suggests that this pathway also plays a role in the regulation of DA contraction in this species. Numerous experimental evidences indicate that chronic hypoxia augments Rho kinase-induced vascular smooth muscle Ca 2ϩ sensitization, particularly in the pulmonary vasculature (13,27) McNamara et al (13) reported that pulmonary vascular RhoA is activated and Rho-kinase activity is increased in rat pups by exposure to hypoxia from birth for 14 d. Moreover, hypoxiainduced RhoA expression in the lung is age dependent and found to be greatest in the fetus (27). In the present study, we observed that the relaxation evoked by Y-27632 and hydroxyfasudil was similar in DAs from normoxic and hypoxic fetuses.…”
Section: Discussionmentioning
confidence: 99%